Some phenotypic characteristics of the Hepu mitten crab, Eriocheir hepuensis Dai, 1991 (Grapsoidea: Brachyura), from Shatt Al-Arab - Jabbar, Intisar M. A.; Najem, Salah M.; Sultan, Entesar N. (Iraqi Journal of Aquaculture, 2021)
Some phenotypic characteristics of the Hepu mitten crabs, Eriocheir hepuensis, were studied, Eighty individuals of the crab males and females were collected from Shatt Al-Arab River. The width of the carapace ranged from 4.2-9.4 cm and 3.4-8.8 cm, and their wet weights ranged from 76.17-299.34 g and 92.27 199.27 g for males and females respectively. The study aims at finding the relationship between the carapace width and wet and dry weights, ash and organic matter as well as finding a relationship between the length of the chela and dry weights, ash and organic matter in the Shatt Al-Arab, as it is now possible to extract the length and width of the carapace without directly calculating them, but by relying on weight. The results showed high significant differences between the width of the carapace with wet and dry weights, ash and organic matter as well as a correlation between the length of cheliped with dry weight and the weight of ash and organic matter. It is noted that there is a strong to weak correlation at the probability level of 0.05 between cheliped length and dry weight ash and organic matter.